Maslahah and its potential role in formation of an Islamic perspective on sociology - Laluddin, Hayatullah; Mohd. Kusrin, Zuliza; Samuri, Mohd. al-Adib (Medwell Journals, 2012)
This study analyses Islamic an Western world views briefly in a comparative perspective and attempts to analyse their influence and effect in the explanation of social phenomenon. It also delineates the two major problems of modern sociology, mainly, lack of universality and lack of applicability to the elemental mistake in the data of human behaviour and its western value orientation. Using both comparative and analytical methods, the researcher make his case for the necessity of drawing an Islamic perspective on sociology, through the application of juristic principle of maslahah from three aspects, from the aspect of provision of material source, introduction of universal values and the endowing of purpose to corpus of sociological knowledge.